A critical review of modern approaches for multidimensional energy poverty measurement. Issue 6 (22nd May 2018) - Pelz, Setu; Pachauri, Shonali; Groh, Sebastian
Abstract : Recent efforts to measure energy poverty more comprehensively attempt to redress the shortcomings of binary metrics that remain in common use. However, significant challenges remain both with the construction of the new measurement frameworks and their application. The paper presents an analysis of recent multidimensional measurement approaches and applications to draw inferences on the implications of applying these for the measurement of energy access and in informing policies aimed at improving it. The assessment suggests that despite progress having been made in capturing the multidimensional nature of energy poverty, the new measures are currently too complex to operationalize at the global level and too prescriptive to gain acceptance in diverse national contexts. Further efforts are thus required to consolidate and simplify the new frameworks for global tracking purposes, and to adapt and modify these to specific country contexts to inform national policy and planning. A subset of key energy poverty dimensions and uniform set of indicators need to be shortlisted for the purposes of global comparisons, while specific national tracking efforts can apply dimensions and thresholds most suited to accurately capture energy poverty and its drivers in a given context. This article is categorized under: Energy Policy and Planning > Economics and Policy Energy and Development > Economics and Policy Energy Infrastructure > Economics and Policy Abstract : Modifying the Multitier Framework for distinct global tracking and national planning purposes.